2010
DOI: 10.3748/wjg.v16.i26.3305
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the surgical treatment of hepatic hydatidosis: Case series with follow-up

Abstract: The most frequently used surgical technique for HH was subtotal cystectomy and the morbidity and mortality rates in this Chilean series are comparable to other national and international series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…[ 1 4 ] Both disability and mortality rates are high in hepatic alveolar echinococcosis with the 10-year mortality rate of 90% as reported. [ 5 , 6 ] Although hepatic alveolar echinococcosis is regarded as a benign disease; however, it is similar to the malignant tumor in terms of invasiveness known as the so-called insect carcinoma and secondary carcinoma’. [ 7 ] This disease has been reported all around the world, especially in the pasturing areas, including Central Europe, Western Europe, Eastern Europe, northern North America, as well as the western part of China.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 4 ] Both disability and mortality rates are high in hepatic alveolar echinococcosis with the 10-year mortality rate of 90% as reported. [ 5 , 6 ] Although hepatic alveolar echinococcosis is regarded as a benign disease; however, it is similar to the malignant tumor in terms of invasiveness known as the so-called insect carcinoma and secondary carcinoma’. [ 7 ] This disease has been reported all around the world, especially in the pasturing areas, including Central Europe, Western Europe, Eastern Europe, northern North America, as well as the western part of China.…”
Section: Introductionmentioning
confidence: 99%
“…El promedio de estancia hospitalaria total fue de 11,5 ± 14,5 días, el cual es mayor a lo reportado en otras series de QL; pero menor a lo reportado en una serie previa de nuestro centro de cirugía de QHH por vía abierta que fue de 16,33 ± 8 días 12 . La mortalidad intraoperatoria ha sido reportada hasta 6% en la cirugía de QHH.…”
Section: Discussionunclassified
“…In 2007, researchers reported that partial hepatectomy was used in France to treat hepatic CE as early as 1965[ 37 ]. With advances in liver surgery, hepatectomy has become one of the main radical treatments for hepatic CE[ 39 ]. Birnbaum et al [ 40 ] proposed that active hepatectomy has advantages over conservative internal capsule removal in the treatment of CE.…”
Section: Mature Stage Of Surgical Treatment For Hepatic Cementioning
confidence: 99%